1996
DOI: 10.1002/(sici)1097-0142(19960801)78:3<527::aid-cncr21>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Phase II evaluation of topotecan for pediatric central nervous system tumors

Abstract: Topotecan administered as a 24-hour infusion every 21 days is inactive in high grade gliomas, medulloblastomas, and brain stem tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…When topoisomerase I is blocked, the DNA strands break and then cancerous cells die. TPT exhibits great activity against human ovarian cancer, cervical and small cell lung cancer (Blaney et al, 1996;Motl et al, 2006;Drummond et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…When topoisomerase I is blocked, the DNA strands break and then cancerous cells die. TPT exhibits great activity against human ovarian cancer, cervical and small cell lung cancer (Blaney et al, 1996;Motl et al, 2006;Drummond et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor activity of topotecan is S-phase-specific and prolonged drug exposure, using a daily lowdose schedule of administration, provides optimal antitumor activity [3,4]. Preclinical and pharmacokinetic studies of topotecan have demonstrated good activity against human brain tumor xenografts, and high cerebrospinal fluid (CSF) penetration providing sound rationale for its use in pediatric brain tumor trials [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Objective responses were seen in retinoblastoma with central nervous system (CNS) metastasis, ependymoma, and rhabdomyosarcoma [12]. At least three additional phase II stud-ies of topotecan in refractory or high-risk pediatric CNS tumors have been reported [6,13,14]. In either 24 or 72-hr intravenous infusions, there were some patients who experienced periods of stable disease (SD), and in fractionated (daily × 10 days) intravenous, pharmacokinetically guided dosing, objected responses were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Two phase II studies of topotecan in children with refractory or high-risk CNS tumors have also been performed [42,43]. Topotecan was inactive in patients with glioblastoma multiforme, brain stem glioma, and medulloblastoma following administration as either a 24-hour CIVI every 3 weeks or a 72-hour CIVI every 3 weeks.…”
Section: Phase II Topotecan Single-agent Studiesmentioning
confidence: 99%